THE CORRELATION BETWEEN KNOWLEDGE OF MARRIAGEABLE AGE, EDUCATION, MATCHMAKING AND CHILD MARRIAGE IN FEMALES IN BANJARNEGARA INDONESIA - Reni Sumanti; Sri Handayani; Dhesi Ari Astuti (Belitung Nursing Journal, 2018)
Background: Teenage marriage is still found in developing countries including in Indonesia. The percentage of teenage marriage in females in Indonesia in 2016 was 11.5%. Various factors related to teenage marriage are education, knowledge, economy, and culture. Impacts caused by teenage marriages include pregnancy in adolescence which results in increased maternal and infant deaths, dropouts, and poor quality of the family. The prevalence of teenage marriage in Banjarnegara in 2016 was 23% higher than the national prevalence. Objective: This study aims to determine the correlation between factors related to knowledge of marriageable age, education, matchmaking and child marriage in females in Banjarnegara Indonesia. Methods: This was a correlational cross-sectional study. There were 96 respondents selected using proportionated stratified random sampling. Chi square and logistic regression were used for data analysis. Results: Findings show that there were statistically significant correlations between knowledge of marriageable age, education and child marriage. There was no significant relationship between matchmaking and child marriage. The respondents with low knowledge were 0.5 times more likely to have child marriage compared with those with high knowledge (p = 0.001, 95% CI = 0.320-0.782). Conclusion: Knowledge of marriageable age was considered as the dominant factor affecting child marriage in Banjarnegara Indonesia. It is suggested that health care providers should continuously promote about the impact of child marriage to increase the knowledge of marriageable age.